Asupan Protein dan Menstruasi dengan Status Anemia Remaja Putri berdasarkan Status Ekonomi di Kabupaten Cianjur (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
Anemia is a micronutrient problems worldwide, especially in developing countries. According to WHO in 2015 the prevalence of anemia in adolescent girls to date ranges from 40-88%. In Indonesia, the prevalence of anemia based on the 2018 Riskesdas is 32% in the 15-24 year age group, with a higher proportion of anemia in women than men. This study aims to determine differences in protein intake and menstruation with anemia status of adolescent girls based on economic status. This research is a quantitative research with an observational analytic approach and a cross sectional design. This research was conducted in Cianjur Regency, West Java Province in November 2019-January 2020. The selection of adolescent subjects was taken based on schools participating in the weekly iron-folate supplementation program from the Cianjur District Health Office which was carried out by purposive sampling with a minimum sample of 56 young women . Data were collected through interviews using a questionnaire. Examination of blood hemoglobin levels was carried out by health laboratory workers in Cianjur Regency using a 301 hemocue. The results showed that there were no differences in hemoglobin levels, duration of menstruation and menstrual cycles in the low and low economic groups high . Then there is no relationship between the length of menstruation and the menstrual cycle with the anemia status of the subject. Furthermore, there are difference intake protein in both groups. Also, there is a relationship between protein intake and anemia status in subjects.